Pathways to rearrest among court mandated female substance use treatment patients. (24th July 2015) - Kopak, Albert M.; Proctor, Steven L.; Hoffmann, Norman G.
<x xml:space="preserve">Abstract</x> Background and objectives Many women who experience substance dependence come into contact with the criminal justice system and are mandated by the court to enter treatment. Treatment is a viable option and can have many positive outcomes, but there remains significant room for improvement. This study was designed to identify key risk factors that can be addressed to improve substance use treatment outcomes for this population. Methods The study sample consisted of (n) 381 women who were court mandated to enter substance use treatment. Multivariate path analyses were conducted to assess the associations between correlates of substance use treatment outcomes, risk for relapse, and rearrest. Results Women who displayed certain demographic risk factors (ie, less educated and unmarried) and had greater levels of substance use severity prior to entering treatment experienced elevated risk for relapse. Consequently, women who relapsed were nearly three times (OR = 2.50, 95%CI = 1.26–4.93) as likely to be rearrested within 12 months of discharge from treatment compared to those who did not relapse. Discussion and Conclusions Certain risk factors contribute to relapse, which increases risk for rearrest. Scientific Significance Services specifically tailored to women who were court mandated to enter treatment need to consider certain demographic risk factors, clinical substance use severity, and relapse prevention as key elements to minimize subsequent criminal offending. (Am J Addict 2015;24:495–498)